Stability Analysis Of Delayed Fractional Integro-Differential Equations With Applications Of RLC Circuits - Mohamed El-Borhamy; Alaa Ahmed (Journal of the Indonesian Mathematical Society, 2020)
This article presents the stability analysis of delay integro-differentialequations with fractional order derivative via some approximation techniques forthe derived nonlinear terms of characteristic exponents. Based on these techniques,the existence of some analytical solutions at the neighborhood of their equilibriumpoints is proved. Stability charts are constructed and so both of the critical timedelay and critical frequency formulae are obtained. The impact of this work into thegeneral RLC circuit applications exposing the delay and fractional order derivativesis discussed.